IMPLEMENTATION OF DECISION SUPPORT SYSTEM FOR SELECTION OF DEPARTMENTS WITH VIKOR METHOD IN SMK PARIWISATA DEPOK - Muhammad Nur; Susliansyah Susliansyah (Jurnal Techno Nusa Mandiri, 2019)
The choice of majors is very important for vocational high school students. There are several factors that influence the decision making of majors. Therefore the writing of this thesis has the purpose of, among others, helping vocational high schools to be able to choose majors in accordance with the wishes and abilities of students. The purpose of writing this thesis is one of the graduation requirements for the Strata Satu (S1) program for the Nusa Mandiri Jakarta (STMIK) program. To achieve the objectives in this study, the authors used quantitative analysis methods. Quantitative analysis in this research is to process the normalization of each criterion value from each alternative that can produce a value and rank in seeing the best majors for students by using the Vise Kriterijumska Optimizacija I Kompromisno Resenje (Vikor) method. Method of Vise Kriterijumska Optimizacija I Kompromisno Resenje (Vikor) helps solve complex problems by determining from the criteria, final score results in vikor and by drawing various considerations to develop weights or priorities.